Characterization of patients admitted to Clínica Dávila under the medical emergency law (ley de urgencia), 2003. - Alvarado, Nelly; Porras, Juan; Alvarado, Manuel (Revista Chilena de Salud Pública, 2007)
Background: The Medical Emergency Law which is currently in force protects life at-risk, irrespectively of the solvency of the patient. Purpose: To carry out a follow-up and to know the characteristics of patients admitted to Clínica Dávila under the protection of the Medical Emergency Law, during 2003. Materials and Methods: A survey was implemented within all inpatients admitted during 2003. Information data was completed with Clínica Dávila database. Results: The total population of inpatients under the protection of the Law was 165. A total of 102 patients were effectively surveyed. Patient mean age was 61; 41.8 % were males while 58.18 % were female. The main diagnoses were cardiovascular diseases (34,5%), neurological disorders (20%), respiratory diseases (14.5%), infectious diseases (7.2%), decompensated Diabetes Mellitus (6%) and surgical pathologies (9.6%). Among the study population, 53.8% of patients were under control for chronic diseases prior to admission; 44.8% of such controls were carried out at primary care outpatient facilities. After discharge, 85.7% of the study population carried out regular controls, in 39.7% of the cases, within the same admission Hospital. A total of 72.72% of the patients deceased after discharge was not undergoing any control, and the median age of such population was 77. Discussion: The results indicate that the main beneficiaries of the Medical Emergency Law were senior patients with a chronic disease who wouldn't be undergoing a sufficient control of their condition. Transfer of patients from the public to the private health system, as well as the impact of the medical assistance delivered by the primary care level are situations that need further research to aim at optimizing the resources available.